Women in politics : gender, power and development - Tadros, Mariz, 1975- (London ; New York : Zed Books, 2014)
Women in Politics offers fresh perspectives on the different spaces, networks, and processes influencing women's political leadership today.
Introduction. Engaging politically : rethinking women's pathways to power / Mariz Tadros -- Politics as service : pathways of district assembly women in Ghana / Takyiwaa Manuh -- Exceptional women : reserved councillors in municipal corporations in Bangladesh / Sohela Hazneen, Iqbal Ehsan and Bayazid Hasan -- Ejecting women from formal politics in the 'old-new' Egypt (2011-12) / Mariz Tadros -- Local power and women's empowerment in a conflict context : Palestinian women contesting power in chaos / Islah Jad -- Pathways to political power in Sudan / Sara Abbas -- Crafting political pathways through the exclusionary Mesh in India / Kanchan Mathur -- Independent candidacy : an alternative political pathway for women in Sierra Leone? / Hussaina J. Abdullah -- Conservative modernization in Brazil : blocking local women's political pathways to power / Ana Alice Alcantara Costa and Andrea Cornwall.
Includes bibliographical references and index.
Print version record.
Added to collection customer.56279.3
Keywords: Women -- Political activity -- Developing countries; Power (Social sciences); Pouvoir (Sciences sociales); Development studies; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; Power (Social sciences); Women -- Political activity; Developing countries